Rice Blast Field Assessment in Three Regencies Underlies the Importance of Fungicide Resistance Studies in West Java, Indonesia: Asesmen Lapangan Penyakit Blas Padi Mendasari Pentingnya Kajian Resistensi Fungisida di Jawa Barat, Indonesia - Khairani, Hagia Sophia; Abe, Ayumi; Sone, Teruo (Jurnal Fitopatologi Indonesia, 2024)
In recent decades, research about rice blast disease in Indonesia has not been focused on the dynamics of the fungus (Pyricularia oryzae) and fungicide use, which resulted in undiscovered pathogen mutations. Observations in Bogor, Cianjur, and Sukabumi Regencies in West Java reveal a high disease incidence (53%–100%), with severity ranging from 8% to 67%. The highest disease severity was recorded in Cikembar District, which is located at the foothill of Mount Gede Pangrango, Sukabumi Regency. Despite a prolonged drought caused by El Niño in 2023, Cikembar still experienced a relatively high disease severity (36%), confirming that this area remains an endemic blast area. The high disease severity, although fungicides were widely used in Cikembar, raises concerns that P. oryzae resistance to fungicides has developed, mainly to isoprothiolane which has been yearly deployed in this area. Farmers are already confronting extra challenges such as unfavorable acidic soil and differences in fungicide use practices decision-making which complicates their control efforts. Laboratory investigations are needed to validate evidence of the emergence of P. oryzae mutations against isoprothiolane in order to provide long-term recommendations for the most effective fungicide use.